PENGARUH PENERAPAN METODE SURVEI, QUESTION, READ, RECITE, REVIEW (SQ3R) TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA DI SEKOLAH DASAR - Hariza Putra, Naufal; Nurmalina, Nurmalina; Aprinawati, Iis; Hana Pebriana, Putri; Fitra Surya, Yenni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of implementing the SQ3R (Survey, Question, Read, Recite, Review) method on students' reading comprehension skills. This research used a pre-experimental design with a One Group Pretest-Posttest Design. The research subjects were all sixth-grade students at SDN 007 Bangkinang Kota, totaling 15 individuals. Data were collected through reading comprehension tests administered before (pretest) and after (posttest) the treatment. Data analysis was conducted using descriptive statistics, normality tests, and hypothesis testing with the Paired Sample T-test via SPSS version 26. The results showed that: (1) The average pretest score was 52.80, with the majority of students (80%) in the very low category; (2) The average posttest score increased to 74.93, with the majority of students (60%) in the moderate category; (3) The hypothesis test results showed a significance value of 0.000 (< 0.05) with t-count = -5.034, indicating a significant difference between the pretest and posttest results. Therefore, the alternative hypothesis (Ha) is accepted, meaning that the implementation of the SQ3R method has a significant effect on improving the reading comprehension skills of sixth-grade students at SDN 007 Bangkinang Kota. Based on these findings, it can be concluded that the SQ3R method is effective in improving students' reading comprehension skills. Teachers are recommended to implement this method as an alternative learning strategy, especially for materials requiring in-depth understanding of reading texts.